Routine Endovascular Treatment With a Stent Graft for Access-Site and Access-Related Vascular Injury in Transfemoral Transcatheter Aortic Valve Implantation. (August 2016) - Sedaghat, Alexander; Neumann, Nils; Schahab, Nadjib; Sinning, Jan-Malte; Hammerstingl, Christoph; Pingel, Simon; Schaefer, Christian; Mellert, Fritz; Schiller, Wolfgang; Welz, Armin; Grube, Eberhard; Nickenig, Georg; et al.
Abstract : Background—: Access-site and access-related vascular injury (ASARVI) is still a major limiting factor in transcatheter aortic valve implantation and affects the outcome of patients. Management strategies for ASARVI include manual compression, stent grafts, and vascular surgery. We hypothesized that the standard use of a self-expanding stent graft for the management of ASARVI is feasible and safe. Methods and Results—: Of 407 patients treated by transfemoral transcatheter aortic valve implantation, 110 experienced ASARVI (27.0%). Of these, 96 (87.3%) were managed by the implantation of a self-expanding nitinol stent graft. In the majority of patients, minor vascular complications triggered the implantation of a stent graft (86.5%), mainly because of bleeding (90.6%) and dissection (5.2%) of the common femoral artery with high rates of primary treatment success (97.9%). Patients receiving stent grafts were more often female (62.2 versus 45.6%, P <0.01), had higher body mass indices (27.8±6.7 versus 25.7±4.7, P =0.01), and suffered more often from diabetes mellitus (34.4 versus 24.5%, P =0.04). Angiographic assessment after a median follow-up of 345 days (interquartile range, 23–745 days) revealed only one patient with moderate, asymptomatic instent-stenosis (1.0%). Compared with a propensity score–matched cohort of patients without ASARVI, stented patients had comparable long-term mortality, despite the occurrence of a vascular complication (1-year mortality: 17.7% versus 26.6%; stent versus matched cohort, respectively; P =0.1). Conclusions—: Routine use of a self-expanding nitinol stent graft in selected patients experiencing ASARVI after transcatheter aortic valve implantation is feasible, safe, and associated with favorable short- and midterm clinical outcome.